Yes‐associated protein 1 mediates initial cell survival during lorlatinib treatment through AKT signaling in ROS1‐rearranged lung cancer. Issue 2 (23rd November 2022) - Yamazoe, Masatoshi; Ozasa, Hiroaki; Tsuji, Takahiro; Funazo, Tomoko; Yoshida, Hiroshi; Hashimoto, Kentaro; Hosoya, Kazutaka; Ogimoto, Tatsuya; Ajimizu, Hitomi; Yoshida, Hironori; Itotani, Ryo; Sakamori, Yuichi; et al.
Abstract: Tyrosine kinase inhibitors (TKIs) that target the ROS proto‐oncogene 1, receptor tyrosine kinase ( ROS1 ) gene have shown dramatic therapeutic effects in patients with ROS1‐rearranged non‐small‐cell lung cancer (NSCLC). Nevertheless, advanced ROS1‐rearranged NSCLC is rarely cured as a portion of the tumor cells can survive the initial stages of ROS1‐TKI treatment, even after maximum tumor shrinkage. Therefore, understanding the mechanisms underlying initial cell survival during ROS1‐TKI treatment is necessary to prevent cell survival and achieve a cure for ROS1‐rearranged NSCLC. In this study, we clarified the initial survival mechanisms during treatment with lorlatinib, a ROS1 TKI. First, we established a patient‐derived ezrin gene‐ROS1‐rearranged NSCLC cell line (KTOR71). Then, following proteomic analysis, we focused on yes‐associated protein 1 (YAP1), which is a major mediator of the Hippo pathway, as a candidate factor involved in cell survival during early lorlatinib treatment. Yes‐associated protein 1 was activated by short‐term lorlatinib treatment both in vitro and in vivo. Genetic inhibition of YAP1 using siRNA, or pharmacological inhibition of YAP1 function by the YAP1‐inhibitor verteporfin, enhanced the sensitivity of KTOR71 cells to lorlatinib. In addition, the prosurvival effect of YAP1 was exerted through the reactivation of AKT. Finally, combined therapy with verteporfin and lorlatinib was found to achieve significantly sustained tumor remission compared with lorlatinib monotherapy in vivo. These results suggest that YAP1 could mediate initial cell resistance to lorlatinib in KTOR71 cells. Thus, combined therapy targeting both YAP1 and ROS1 could potentially improve the outcome of ROS1‐rearranged NSCLC. Abstract : YAP1 activation during lorlatinib treatment mediates initial cell survival in response to lorlatinib via AKT signaling in ROS1‐rearranged lung cancer. Combinatorial therapy targeting both YAP1 and ROS1 may potentially improve the outcome of ROS1‐rearranged lung cancer.